Factors Influencing Millennials and Generation Z's Trust in Crypto-Based Payments in Indonesia - Felicia Hanisentana; Hendra Achmadi (Journal of Social Research, 2025)
Cryptocurrency adoption in Indonesia is rising, yet trust barriers persist, particularly among Millennials and Gen Z. Despite growing transaction volumes (IDR 475.13 trillion by 2024), gaps remain in understanding trust drivers specific to this demographic. This study investigates factors influencing trust in crypto-based payments, testing hypotheses on privacy, anonymity, traceability, expectations, and satisfaction. A quantitative cross-sectional design surveyed 195 Indonesian respondents (purposive sampling) using PLS-SEM analysis in SmartPLS 4.0, assessing measurement and structural models, predictive relevance, and IPMA. Trust significantly boosts adoption intention (t = 20.279, p = 0.000), driven by expectations (t = 5.898) and satisfaction (t = 2.096), while privacy, anonymity, and traceability showed no significant impact. IPMA revealed trust as high-importance but low-performance, urging strategic improvements. Results guide policymakers and businesses to prioritize transparency, user experience, and education over privacy-centric features. Future research should expand demographics, integrate qualitative methods, and compare crypto with other payment systems (e.g., CBDCs).